The Cluster Ages Experiment (CASE) – IX. Analysis of four detached eclipsing binaries in the globular cluster NGC 3201. Issue 2 (28th September 2022) - Rozyczka, M; Thompson, I B; Dotter, A; Mazur, B; Narloch, W; Pych, W; Hełminiak, K G; Moharana, A; Beletsky, Y; Burley, G S; Marshall, J L; Morrell, N; et al.
ABSTRACT: We use photometric and spectroscopic observations of four detached eclipsing binaries in the globular cluster NGC 3201 to derive masses, radii, and luminosities of the component stars. Spanning across almost three magnitudes in the colour–magnitude diagram, the components offer a unique possibility to test the theory of stellar evolution. Their masses, radii, and luminosities range from 0.66 to 0.84 M ⊙, 0.68 to 2.46 R⊙, and 0.38 to 5.56 L ⊙, respectively. The distance to the cluster measured from the distance moduli of the component stars amounts to 4.54^+0.11_-0.14 kpc and agrees with the recent estimate based on Gaia parallaxes. By comparing the M − R and M − L diagrams of the component stars and the colour–magnitude diagram of NGC 3201 to Dartmouth model isochrones, we estimate the most probable age of the cluster to be 11.5 ± 0.5 Gyr. This estimate is based on three binaries only, as the fourth one seems to evolve along a different path, probably due to non-standard chemical composition and/or history. We confirm the tendency, observed in earlier CASE papers, for the age indicated by the M − R diagram to be younger than that implied by the colour–magnitude diagram.